Вып. 3: Творческий характер отражения / [под редакцией М. Н. Руткевича] - Руткевич Михаил Николаевич (1974)
Экземпляры: КХ (20231024) / Инвентарный номер: 594484 / Сис.шифр: 1М / Авт.знак: Л 45 / ГРНТИ: 02 / ББК: 87